JUMLAH ERITROSIT PADA PENDERITA GAGAL GINJAL YANG ANEMIA - Andri Sukeksi; Afrida Yulsi Prafiyahesa (Prosiding Seminar Nasional Unimus, 2023)
Anemia can happen when somebody Already experience decline Work kidney to 20 to 50 percent fromfunction normal kidney Anemia in patients fail kidney happen because production erythropoietin in theaffected kidney decline or shorten it age cell blood red, and lack deficient nutrition in patients. Knowdescription amount patient's erythrocytes fail anemic kidney. Establish amount erythrocytes done use tooltest amount erythrocytes in working blood automatically with results prediction more precision, accuracy,and calibrated. Results research that has performed at Roemani Hospital use sample sufferer fail kidney asmany as 20 samples patient obtained results amount erythrocytes low below 4.0-5.6 million /ul in malesman whereas Woman obtained results below 3.9-5.1 million / ul. Based on patient level fail anaemia kidneyswere found amount erythrocytes experience reduction in mild anemia, some factor risk can causeabnormality where decline function work kidney in a manner fast or progressive so that raises complaintfrom light until heavy condition the named with fail kidney chronic (CKD). Result sum erythrocytes inpatients with anemia kidney the lowest is 2.0 million /ul and the highest is 3.8 million /ul with an averageof 2.7 million /ul. Based on type sex in patients with anemia kidney more Lots man with amount averageerythrocyte is 2.7 million / ul. Amount erythrocytes based on level in mild anemia 2.2 million / ul and inmoderate anemia 2.9 million / ul, more and more light anemia so the more low amount producederythrocytes.Keywords: How to check, the number of erythrocytes